Modified Idea Listing Technique with Flash Card to Increase Students’ Writing Ability towards EFL Learners - Asrofi, Ahmad (CV. Tripe Konsultan, 2024)
The aim of this study was to find out the significant difference in modified the idea listing technique (ILT) with flash card toward the students’ writing ability. The quantitative research would be conducted in this research and the participants would be focused in the eighth grade of MTs Raudhotul Jannah, Central Lampung. The data would be gained by contributing the pre-test and post- test. Then, to collect the data, it was analyzed by using SPSS version 25.0. The data was analyzed by using paired samples T-test. The result showed that mean of post-test is higher than pre-test and two tail significance is .000 which is lower than α = .05 (p = .000 < α = .05). As a result, the hypothesis is accepted. It is revealed that the modified ILT with flash card is one of the factors which influences the students’ writing ability. Therefore, the result of this research showed that by using modified ILT with flash card, it was more significant differences in teaching writing ability. Furthermore, the writing aspects of modified ILT can increase in students’ writing ability. So, it can be concluded that modified ILT with flash card can increase the students’ writing ability.